2018
DOI: 10.22159/ijpps.2018v10i2.22472
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Drug Therapy Problems in Asthma Patients Receiving Care in Two Hospitals in South-Eastern Nigeria

Abstract: Objective: To evaluate drug therapy problems in asthma patients visiting a secondary and tertiary hospital in South-Eastern Nigeria.Methods: This study was a retrospective, cross-sectional analyses of the medical records of adult asthmatic patients receiving care in two hospitals in Enugu State, within a 15-year period. The Pharmaceutical Network Care Europe (PCNE) tool version 6.2 was used to assess drug therapy problems. The IBM Statistical Product for Services Solution (SPSS) version 20.0 was used for analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…While unnecessary drug therapy was the most common class of TRP, accounting for ~67% of all the TRPs at discharge, previous studies showed treatment effectiveness or adverse drug reactions to be the most common treatment problems [ 12 , 38 ]. In this line, most of the study cases were shown to receive duplication of inhaled corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…While unnecessary drug therapy was the most common class of TRP, accounting for ~67% of all the TRPs at discharge, previous studies showed treatment effectiveness or adverse drug reactions to be the most common treatment problems [ 12 , 38 ]. In this line, most of the study cases were shown to receive duplication of inhaled corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…Estudos identificando PRMs exclusivamente em utentes idosos com asma ainda são escassos, dificultando uma comparação mais precisa entre os achados. No entanto, já está bem documentado que na população com asma, os principais PRMs identificados estão relacionados com a administração dos medicamentos e aos esquemas terapêuticos inadequados (Amorha et al, 2018;Farias et al, 2016). Dantas et al, (2019), em um estudo de acompanhamento farmacêutico em utentes ambulatoriais com asma, detectaram como PRM prevalente aquele relacionado ao cumprimento do regime terapêutico ou adesão ao tratamento, causado pelo não entendimento da técnica correta no uso dos medicamentos inalatórios (broncodilatadores e corticosteroides).…”
Section: Problemas Relacionados a Medicamentos E Intervenções Farmacêuticasunclassified